2003
DOI: 10.1097/01.mp.0000085760.74313.dd
|View full text |Cite
|
Sign up to set email alerts
|

The p16 (CDKN2a/INK4a) Tumor-Suppressor Gene in Head and Neck Squamous Cell Carcinoma: A Promoter Methylation and Protein Expression Study in 100 Cases

Abstract: The p16 (CDKN2a/INK4a) gene is an important tumor-suppressor gene, involved in the p16/cyclindependent kinase/retinoblastoma gene pathway of cell cycle control. The p16 protein is considered to be a negative regulator of the pathway. The gene encodes an inhibitor of cyclin-dependent kinases 4 and 6, which regulate the phosphorylation of retinoblastoma gene and the G1 to S phase transition of the cell cycle. In the present study, p16 gene promoter hypermethylation patterns and p16 protein expression were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
71
0
6

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 16 publications
3
71
0
6
Order By: Relevance
“…The lack of cyclin D mediated phosphorylation of the retinoblastoma (Rb) protein results in the inactivation of the cell cycle in phase G1 [17]. Several reports suggest that reduced expression or the lack of p16 ink4 protein correlates with poor prognosis of HNSCC [18,19], which we confirmed in our tested patient cohort. Recent reports have revealed that p16 ink4 -expression is associated with HPV-positivity, implying that p16 ink4 can be a surrogate marker for HPV detection.…”
Section: Discussionsupporting
confidence: 77%
“…The lack of cyclin D mediated phosphorylation of the retinoblastoma (Rb) protein results in the inactivation of the cell cycle in phase G1 [17]. Several reports suggest that reduced expression or the lack of p16 ink4 protein correlates with poor prognosis of HNSCC [18,19], which we confirmed in our tested patient cohort. Recent reports have revealed that p16 ink4 -expression is associated with HPV-positivity, implying that p16 ink4 can be a surrogate marker for HPV detection.…”
Section: Discussionsupporting
confidence: 77%
“…In one case, p16 protein expression is accompanied by positive p16 promoter methylation (Table 1). This has been previously documented in another study 18 and could be due to intratumor heterogeneity of methylation pattern or the presence of minor component of tumor cells that showed epigenetic silencing of the p16 gene. Nevertheless, these results indicate that approximately Figure 4 DNA sequence of methylation-specific PCR products: W, a wild-type DNA sequence; U, bisulfite-modified unmethylated DNA sequence.…”
Section: Discussionmentioning
confidence: 91%
“…Known positive and negative cases from our previous studies on head and neck carcinoma were used as control. 18 Two pathologists (QH and CYF) evaluated the immunohistochemical staining results independently.…”
Section: Immunohistochemical Staining For the P16 Proteinmentioning
confidence: 99%
“…The frequency of methylation was found to be approximately 30% in head and neck squamous cell carcinoma specimens obtained from surgically removed tumors (1)(2)(3)(4)(5)(6)(7)(8)(9). Although several reports have described the hypermethylation of the promoter region of the p16 tumor suppressor gene in oral cancer and in cancers of the pharynx and larynx, there have not been any reports which point out differences in the frequencies of the methylation among those cancers.…”
Section: Discussionmentioning
confidence: 94%